International symposium on ceramic materials and components for engines - International Symposium on Ceramic Materials and Components for Engines (4th : 1991 : Goteborg, Sweden); Carlsson, R.; Johansson, T.; Kahlman, L. (London : Elsevier Applied Science, 1992)
22